Event-Based Planning for Multicultural Education in Vocational High Schools: Evidence from Bakti Karya Parigi Pangandaran, Indonesia - Irpan Ilmi; Dian Dian; Hasan Basri; Ajid Thohir (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to explore effective planning strategies for multicultural education through an event management framework at Bakti Karya Parigi Vocational High School (SMK). Using a qualitative research approach with grounded theory methodology, this study employs a case study design. Data were collected through in-depth interviews with the school principal, teachers, students, and stakeholders; participant observation during the planning and implementation of school events; and document analysis. Data were managed and analyzed using ATLAS—ti software. The findings reveal that SMK Bakti Karya Parigi adopts event management as a holistic educational strategy to instill multicultural values. The school systematically plans and implements activities that introduce cultural diversity and build students' character and competencies for a multicultural society. This study concludes that event management principles—such as idea exploration, resource planning, collaboration, financial management, targeted promotion, and operational planning—can be effectively integrated into multicultural education. This finding recommends that vocational schools adopt event-based strategies as a sustainable model for fostering inclusivity and intercultural competence in diverse educational environments.